Bioakumulasi Logam Besi (Fe) dan Seng (Zn) pada Ikan Bandeng (Chanos chanos) di Keramba Jaring Tancap Kelurahan Tanjung Mas, Semarang - Arza, Alfira; Tri Martuti, Nana Kariada (Universitas Negeri Semarang, 2023)
Heavy metal contamination can cause a decrease in the quality of the aquatic environment which will have an impact on the quality of milkfish farmed in stick-net cages (KJT) by the local community. This Study aimed to analyze the Fe and Zn content in water and their bioaccumulation in Chanos chanos cultivated at KJT Tanjung Mas, Semarang. This research was conducted using explorative methods. The samples were taken by a random purposive sampling. Analysis of the content of heavy metals Fe and Zn in water samples and milkfish meat by atomic absorption spectrophotometry. The results of the three research stations showed that the concentration of Fe in water was 0.0270 – 0.0367 mg/L and Zn was in the range of 0.0050 – 0.0077 mg/L. The content of Fe and Zn in the waters of Tanjung Mas still in accordance with the quality standards of the Government Regulation of the Republic of Indonesia. The content of Fe contained in milkfish meat is 15.487 – 18.893 mg/kg, which exceeds the limit set by SNI (2009). The Zn content in milkfish meat is 11,504 – 12,568 mg/kg, which is below the limits of food security regulation in Ditjend POM. The conclusion of this study is that the heavy metal content of Fe and Zn in KJT Tanjung Mas waters and the heavy metal content of Zn in milkfish meat are below the threshold, while the heavy metal content of Fe in milkfish meat has exceeded the threshold.